217k views
3 votes
Use only positive exponents (4vy^-9) * (2x^-6 x^6 y^6) * (3v^4)

User Sheresa
by
5.9k points

1 Answer

5 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ (4vy^(-9))\cdot (2x^(-6)x^6y^6)\cdot (3v^4)\implies 4vy^(-9)2x^(-6)x^6 y^6 3v^4 \\\\\\ 4\cdot 3\cdot 2vv^4y^(-9)y^6x^(-6)x^6 \implies 24v^(1+4)y^(-9+6)x^(-6+6)\implies 24v^5y^(-3)x^0 \\\\\\ 24v^5\cdot \cfrac{1}{y^3}\cdot 1\implies \cfrac{24v^5}{y^3}

User Jeff Tilton
by
5.6k points